2015
DOI: 10.1080/00224545.2015.1064347
|View full text |Cite
|
Sign up to set email alerts
|

Who Would Do That? A Theory-Based Analysis of Narratives of Sources of Family Ostracism

Abstract: There are many benefits derived from families, but not all family members are loving and accepting. Family members may act as sources of ostracism (people or groups who ostracize another person/group). We suggest sources engage in family ostracism for extended periods, their motives fit with prior theoretical models, and trait-level forgiveness may help understand source behavior. We analyzed data from 63 narratives and questionnaires to investigate the motives, power dynamics, and psychological correlates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…All of this suggests that ostracizing close others may be qualitatively different than ostracizing acquaintances and casual friends (see Poulsen & Carmon, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…All of this suggests that ostracizing close others may be qualitatively different than ostracizing acquaintances and casual friends (see Poulsen & Carmon, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Social exclusion can occur in either of these situations: a person can say no to a wedding invitation and can choose to end a decade-long friendship. Research has robustly shown that targets of social exclusion suffer a variety of negative effects (e.g., Leary, 1990 ; Baumeister et al, 2002 ; Williams, 2007a , b ; Slavich et al, 2010 ; DeWall and Bushman, 2011 ; Williams and Nida, 2011 ) but less is known about the sources of rejection (e.g., Poulsen and Kashy, 2012 ; Legate et al, 2013 ; Wesselmann et al, 2013 ; Zadro and Gonsalkorale, 2014 ; however, for a recent discussion of sources of ostracism, specifically, see Gooley et al, 2015 ; Grahe, 2015 ; Legate et al, 2015 ; Nezlek et al, 2015 ; Poulsen and Carmon, 2015 ; Van Tongeren et al, 2015 ; Wesselmann et al, 2015 ; Wirth et al, 2015 ). If one potential goal of research on exclusion is to minimize exclusion’s negative effects, then psychologists need to investigate exclusion from both the target and source’s point of view.…”
Section: Introductionmentioning
confidence: 99%
“…defensive ostracism) or because they might dislike something the target did (i.e. punitive ostracism; Poulsen and Carmon, 2015). Ostracism need not be intentional, however.…”
Section: Ejm 529/10mentioning
confidence: 99%
“…Although some may think it is an extreme or infrequent event, people experience about one ostracism episode every day (Nezlek et al, 2015). Individuals are ostracised in interpersonal friendships and relationships (Poulsen and Carmon, 2015), by close others or strangers (Nezlek et al, 2012), by in-group or out-group members (G omez et al, 2011), online (Wolf et al, 2015), in workplaces (Scott et al, 2013;Wu et al, 2011) and in marketplaces (Mattila et al, 2013;Mead et al, 2011).…”
Section: Ejm 529/10mentioning
confidence: 99%